The Implementation of Authentic Assessment in Grade 9 Students' Writing of Procedure Text at MTs Swasta Al-Washliyah Tanjung Morawa - Neni Afrida Sari Harahap; Dwi Pradani (Invention: Journal Research and Education Studies, 2026)
This study investigates the implementation of authentic assessment in teaching writing procedure texts to ninth-grade students at MTs Swasta Al-Washliyah Tanjung Morawa. The aims of this research are to identify the aspects of authentic assessment implemented in the procedural text writing activities, and to describe how authentic assessment is applied in the classroom practice. The data and sources were collected from ten ninth-grade students who had actively participated in English learning and had experience writing procedural texts. The primary techniques and instruments used was a closed-ended Yes/No questionnaire comprising 10 questions. This instrument was systematically designed based on Hughes' (2003) five aspects of assessment, namely validity, reliability, administration, discrimination, and backwash effect. The data analysis was conducted using an interactive analysis model (Ratnaningtyas et al., 2023), involving three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that the implementation of authentic assessment was partially successful. Students reported high levels of validity, as writing tasks aligned with their real-life experiences and abilities. The backwash effect was notably positive, with all students receiving constructive feedback from the teacher. The assessment also demonstrated good discriminatory power. However, reliability was less consistent, with students' perceptions of rubric use being uneven. The implementation showed weaknesses in process and holistic assessment, where teachers focused more on the final product than the overall writing process and did not fully integrate attitude assessment. These findings imply that a more systematic approach is needed to ensure consistent rubric use and incorporate process-based evaluation.